EFFECTIVENESS OF BACILLUS THURINGIENSIS AS A BIOCONTROL AGENT AGAINST ROOT-KNOT NEMATODES ON TOMATO PLANT - Saad T. A. Yass,; Khalid M. Al-Juhaishi,; Sarah Tareq Hasan,; Deepak K. Sinha, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to evaluate the nematicidal effect of three local Bacillus thuringiensis isolates in controlling the root-knot nematodes Meloidogyne spp. under laboratory and shade house conditions. We amplified 16S rRNA and performed polymerase chain reaction on the isolates to confirm them as B. thuringiensis. PCR was carried out with a universal primer for the 16S rRNA amplification for confirmation, where all three isolates yielded the predicted amplicon. The isolates were identified as B. thuringiensis and documented using sequencing based on their 16S rRNA genes. Sequencing results were deposited at NCBI. The laboratory experiments revealed that Sa.Sa.Kh.3 isolate outperformed the other two isolates, Sa.Sa.Kh.1 and Sa.Sa.Kh.2, in terms of egg hatching inhibition and second-stage juvenile mortality, reached 94.33% and 90% after 72 hours of exposure, respectively. Pot trial showed that the Sa.Sa.Kh.3 isolate reduced root gall index and improved plant growth parameters shoot fresh weight, shoot dry weight, root fresh weight, root dry weight, plant height, and root length of tomato plants by 1.33g, 77.00 g, 16.63 g, 12.15 g, 2.77 g, 88.00 cm, and 34.33, respectively, when compared to the control groups. Results showed that all isolates, both pre-nematode inoculation and post-nematode inoculation, revealed significant effects on root gall index and enhanced plant growth parameters compared to control groups.